Chinese-American Relations in the Asia-Pacific Region - I. Denisov (Международная аналитика)
The article discusses modern state of Chinese-American relations under the conditions of simultaneous existence of rivalry and cooperation between two countries in the Asia-Pacific region. Up to the author’s view relations between China and USA depend increasingly on poor-predictable and fast-changing situation in the region. Facing difficulties in direct military containment, USA reveal certain flexibility in building relations with China. While establishing mechanisms of global control, China is not ready to change the mode of conduct immediately. For forecast of the future Sino-American relations the analysis of situation in the South China sea is of crucial importance.